STRATEGI KOMUNIKASI PEMASARAN KOPI DENGAN PEMANFAATAN MEDIA SOSIAL - Prabawa, Bagus Ade Tegar; Adisastra, I Nyoman Surpa; Purnama Yasa, I Komang Widya (IAHN Gde Pudja Mataram, 2023)
In Colol villages, located in East Manggarai Regency, coffee cultivation has become a key source of income for locals to meet their daily requirements. Farmers sell their coffee produce to collectors or other marketing institutions, which necessitates expenses on their part. They receive income from the sale of their coffee. The quantity of coffee produced, be it high or low, has an impact on the farmers' earnings. Therefore, the utilization of social media, like sisal media, is expected to boost the coffee marketing income of farmers. The aim of this research is to ascertain the complete coffee marketing process and the effectiveness of social media in coffee marketing. There are two coffee marketing channels: through coffee farmers, large traders, and exporters, or through social media. After analyzing marketing expenses, selling and buying prices, and the profits of each marketing institution involved.